18x-4(3x+4)=(9x-5)-5(3x+7)

Simple and best practice solution for 18x-4(3x+4)=(9x-5)-5(3x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x-4(3x+4)=(9x-5)-5(3x+7) equation:


Simplifying
18x + -4(3x + 4) = (9x + -5) + -5(3x + 7)

Reorder the terms:
18x + -4(4 + 3x) = (9x + -5) + -5(3x + 7)
18x + (4 * -4 + 3x * -4) = (9x + -5) + -5(3x + 7)
18x + (-16 + -12x) = (9x + -5) + -5(3x + 7)

Reorder the terms:
-16 + 18x + -12x = (9x + -5) + -5(3x + 7)

Combine like terms: 18x + -12x = 6x
-16 + 6x = (9x + -5) + -5(3x + 7)

Reorder the terms:
-16 + 6x = (-5 + 9x) + -5(3x + 7)

Remove parenthesis around (-5 + 9x)
-16 + 6x = -5 + 9x + -5(3x + 7)

Reorder the terms:
-16 + 6x = -5 + 9x + -5(7 + 3x)
-16 + 6x = -5 + 9x + (7 * -5 + 3x * -5)
-16 + 6x = -5 + 9x + (-35 + -15x)

Reorder the terms:
-16 + 6x = -5 + -35 + 9x + -15x

Combine like terms: -5 + -35 = -40
-16 + 6x = -40 + 9x + -15x

Combine like terms: 9x + -15x = -6x
-16 + 6x = -40 + -6x

Solving
-16 + 6x = -40 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-16 + 6x + 6x = -40 + -6x + 6x

Combine like terms: 6x + 6x = 12x
-16 + 12x = -40 + -6x + 6x

Combine like terms: -6x + 6x = 0
-16 + 12x = -40 + 0
-16 + 12x = -40

Add '16' to each side of the equation.
-16 + 16 + 12x = -40 + 16

Combine like terms: -16 + 16 = 0
0 + 12x = -40 + 16
12x = -40 + 16

Combine like terms: -40 + 16 = -24
12x = -24

Divide each side by '12'.
x = -2

Simplifying
x = -2

See similar equations:

| 15xy-30y= | | 3d-2d-d+2d=8 | | F=1/2kw | | 3s-42=33 | | 6(c+2)=5(1-3c) | | 1x/5=14 | | 6[x+2]=60 | | 10d-7d=9 | | -x^3+3x+1.5=0 | | 4(1-7n)-5= | | d/7+75=81 | | -x^3+3x-1.5=0 | | 3(x-4)-2=5x | | 0.2(15y+2)=0.5(8y-3) | | 3x(x+17)=0 | | 1/2(3x=6)=3(x-2) | | 6x-5+2x=12 | | Y/6-7 | | 7sqrt(x-3)-2=8 | | m^2-h^2= | | Z-(11+3z)3=22-8z | | 3/8- | | 20y^2-2y-4=0 | | log(7)*7=1 | | 80=3x | | -181+2x=12x+79 | | 15u-12u=18 | | 110/28 | | 5(4x-2)+6=-1 | | 2(x-6)+5=3(2x-4) | | 6xy/16y | | 5+4g=7 |

Equations solver categories